Predictors of Parent Engagement in Community-Based Parent–Child Interaction Therapy: A Brief Report. (March 2023) - Nathanson, Emma W.; Rispoli, Kristin M.; Piper, Rachel; Naguib, Suzi
Despite substantial empirical support, correlates of retention and success in community-based parent–child interaction therapy (PCIT) implementation are not well defined. Widespread application of PCIT necessitates improved understanding of intervention components relating to family outcomes beyond highly controlled research trials. Using data collected as part of routine care, this study examined homework completion, time in intervention, and parent perceptions of pre-intervention behavioral issues as predictors of PCIT completion in a community-based sample. Subjects included 78 parents (49 women and 29 men) of 45 children (20 girls, 25 boys; mean age = 5.53 years) participating in PCIT in an outpatient behavioral health clinic in a small Midwestern U.S. city. Unlike previous controlled trials, homework completion did not predict child behavior growth or intervention completion. Reasons for early termination were examined thematically, and parent stress emerged as a possible avenue for future intervention in helping parents successfully complete PCIT. The issue of intervention dosage was also explored to see if families who prematurely terminated from PCIT still evidenced gains in child behavior.